Effect of Low dose Radiation on Differentiation of Bone Marrow Cells into Dendritic Cells - Sung Hak Chun; Ga-Young Park; Yu Kyeong Han; Sung Dae Kim; Joong Sun Kim; Chang Geun Lee; Kwangmo Yang (SAGE Publishing, 2013)
Low dose radiation has been shown to be beneficial to living organisms using several biological systems, including immune and hematopoietic systems. Chronic low dose radiation was shown to stimulate immune systems, resulting in controlling the proliferation of cancer cells, maintain immune balance and induce hematopoietic hormesis. Since dendritic cells are differentiated from bone marrow cells and are key players in maintaining the balance between immune activation and tolerance, it may be important to further characterize whether low dose radiation can influence the capacity of bone marrow cells to differentiate into dendritic cells. We have shown that bone marrow cells from low dose-irradiated (γ-radiation, 0.2Gy, 15.44mGy/h) mice can differentiate into dendritic cells that have several different characteristics, such as expression of surface molecules, cytokine secretion and antigen uptake capacity, when compared to dentritic cells differentiated from the control bone marrow cells. These differences observed in the low dose radiation group can be beneficial to living organisms either by activation of immune responses to foreign antigens or tumors, or maintenance of self-tolerance. To the best of our knowledge, this is the first report showing that total-body low dose radiation can modulate the capacity of bone marrow cells to differentiate into dendritic cells.